Justicia segoviaensis, a new name for Justicia micrantha (Oerst.) V.A.W.Graham (Acanthaceae) - Soumya, Puliyakode; Sunojkumar, Purayidathkandy (Phytotaxa, 2018)
Justicia micrantha (Oerst.) Graham (1988: 603) is a Central American species originally described by Oersted as Chaetothylopsis micrantha Oersterd (1855: 163). However, it is illegitimate name under Art. 53.1 of the ICN (McNeill et al., 2012) because an earlier homonym Justicia micrantha Wall. ex Clarke (1885: 536) already exist for another Indian plant. Therefore, a new name, Justicia segoviaensis, is proposed here for the later homonym, J. micrantha (Oerst.) V.A.W. Graham.